The matching book embeddings of pseudo-Halin graphs - Zeling Shao; Yanling Hu; Huiru Geng; Zhiguo Li (Electronic Journal of Graph Theory and Applications (EJGTA), 2023)
The book embedding of a graph G is to arrange the set of points of the graph on a line (spine) and embed the edges on the half-plane bounded by the spine so that the edges in the same page do not intersect with each other. If the maximum degree of vertices in each page is 1, the book embedding is matching book embedding. The matching book thickness of G is the minimum number n that G can be matching book embedded in n-page. In this paper, the matching book thickness of pseudo-Halin graphs is determined.